Impact of clinical pharmacist intervention in the treatment of pemphigus with rituximab at a tertiary care hospital - J., Subadradevi; S. M., Arthi (International Journal of Research in Medical Sciences, 2024)
Background: Pemphigus is an autoimmune bullous disease that causes lesions and blisters over skin and mucous membrane. Treatment involves long-term administration of systemic corticosteroids and/or other immunosuppressive agents. Rituximab is a type of monoclonal antibody target specific cells in the body. PDAI score is used to measure the extent of pemphigus. DLQI questionnaire is used to interpret the quality of life. Aim was to evaluate the impact of clinical pharmacist intervention in the treatment of pemphigus with rituximab. Methods: A prospective interventional study was carried out in dermatology department. 40 patients diagnosed with pemphigus were included in the study. The demographic data, lab parameters, PDAI score and DLQI questionnaire were collected before and after infusion and pharmacist intervention. The data were statistically analyzed using paired t-test. Results: Females represented the majority of the study population. The mean±SD of age was found to be 44.57±12.90. During rituximab administration majority of the patients experienced no adverse events. Notably, hypertension emerged as the most commonly reported adverse effect. Before the intervention, the mean±SD for PDAI was found to be 29±19.78 and DLQI was found to be 9.55±4.32. After the intervention, the mean±SD for PDAI was found to be 24.25±18.13 and DLQI was found to be 7.925±3.99. The values are analyzed using paired t-test and have significance with p value <0.0001. Conclusions: Clinical pharmacist intervention regarding treatment, disease and life style modification having a significant improvement in patients with pemphigus.